Intimate partner violence and breastfeeding practices: a systematic review of observational studies - Raquel de Souza Mezzavilla; Marina de Figueiredo Ferreira; Cintia Chaves Curioni; Ana Cristina Lindsay; Maria Helena Hasselmann (Elsevier, 2018)
Objective: To review the association between intimate partner violence and breastfeeding practices in the literature. Data sources: The search was carried out in five databases, including MEDLINE, LILACS, SCOPUS, PsycoINFO, and Science Direct. The search strategy was carried out in February 2017. The authors included original studies with observational design, which investigated forms of intimate partner violence (including emotional, physical, and/or sexual) and breastfeeding practices. The quality of the studies was assessed based on the bias susceptibility through criteria specifically developed for this review. Summary of data: The study included 12 original articles (10 cross-sectional, one case-control, and one cohort study) carried out in different countries. The forms of intimate partner violence observed were emotional, physical, and/or sexual. Breastfeeding was investigated by different tools and only assessed children between 2 days and 6 months of life. Of the 12 studies included in this review, eight found a lower breastfeeding intention, breastfeeding initiation, and exclusive breastfeeding during the first six months of the child's life, and a higher likelihood of early termination of exclusive breastfeeding among women living at home where violence was present. The quality varied between the studies and six were classified as having low bias susceptibility based on the assessed items. Conclusions: Intimate partner violence is associated with inadequate breastfeeding practices of children aged 2 days to 6 months of life. Resumo: Objetivo: Revisar na literatura a associação da violência entre parceiros íntimos e as práticas de aleitamento materno. Fontes dos dados: Foram utilizadas para as buscas cinco bases de dados, incluindo o MEDLINE, LILACS, SCOPUS, PsycoINFO e Science Direct. A estratégia de busca foi realizada em fevereiro de 2017. Foram incluídos estudos originais com desenho observacional, os quais investigaram formas de violência entre parceiros íntimos: emocional, física e/ou sexual e as práticas de aleitamento materno. A qualidade dos estudos foi avaliada a partir da susceptibilidade a vieses por critérios especificamente desenvolvidos para esta revisão. Síntese dos dados: Foram incluídos 12 artigos originais (10 seccionais, 1 caso-controle e 1 coorte) realizados em diferentes países. As formas de violência entre parceiros íntimos observadas foram emocional, física e/ou sexual. O aleitamento materno investigado nos estudos se fez por diferentes instrumentos e avaliaram apenas crianças entre dois dias e seis meses de vida. Dos doze estudos incluídos nesta revisão, oito encontraram menor chance de intenção de amamentar, menor chance de iniciação ao aleitamento materno e de amamentação exclusiva durante os primeiros seis meses de vida da criança e maior probabilidade de interrupção precoce do aleitamento materno exclusivo entre as mulheres que viviam em domicílios onde a violência estava presente. A qualidade variou entre os estudos e seis foram classificados apresentando baixa suscetibilidade ao viés a partir dos itens julgados. Conclusões: A violência entre parceiros íntimos está relacionada às práticas inadequadas de aleitamento materno de crianças entre dois dias e seis meses de vida. Keywords: Breastfeeding, Human milk, Intimate partner violence, Domestic violence, Review, Palavras-chave: Amamentação, Leite humano, Violência entre parceiros íntimos, Violência doméstica, Revisão